Vitamin D Binding Protein, Total and Free Vitamin D Levels in Different Physiological and Pathophysiological Conditions - David Bikle, Daniel (Frontiers Media SA, 2021)
There is a high prevalence of vitamin D deficiency worldwide, but how to define vitamin D deficiency is controversial. Currently, the plasma concentration of total 25-hydroxyvitamin D [25(OH)D] is considered an indicator of vitamin D status. The free hormone hypothesis states that protein-bound hormones are inactive while unbound hormones are free to influence biological activity. The majority of circulating 25(OH)D and 1,25(OH)2D is tightly bound to vitamin D binding protein (DBP), 10 -15% is bound to albumin, and less than 1% of circulating vitamin D exists in an unbound form. While DBP is relatively stable in most healthy populations, recent studies have shown that there are gene polymorphisms associated with race and ethnicity that could alter DBP levels and binding affinity. Furthermore, in some clinical situations total 25(OH)D levels are altered, and knowing whether DBP is also altered may have implications for diagnosis and treatment. In this Research Topic, we provide a collection of comprehensive research on vitamin D and DBP metabolism among different ethnic population and patients with different diseases.